Teaching​ Information Literacy and Writing Studies Volume 2, Upper-Level and Graduate Courses - Veach, Grace (Purdue University Press, 2019)
This volume, edited by Grace Veach, explores leading approaches to teaching information literacy and writing studies in upper-level and graduate courses. Contributors to the volume describe cross-disciplinary and collaborative efforts underway across higher education, during a time when "fact" or "truth" is less important than fitting a predetermined message. Topics include: working with varied student populations, teaching information literacy and writing in upper-level general education and disciplinary courses, specialized approaches for graduate courses, and preparing graduate assistants to teach information literacy.